Effect of Local Site Conditions on Earthquake Ground Motions in Hanoi: Results from Numerical Simulations - Trung, Giang Kien; Nguyen, Pham Dinh; Vinh, Nguyen Duc (VNU Journal of Science: Mathematics - Physics; Vol 38 No 2DO - 10.25073/2588-1124/vnumap.4684, 2022)
This paper presents some numerical simulation results on the influence of local site conditions on earthquake ground motions in Hanoi. Numerical simulation method through DEEPSOIL program was used in the study. Geological data of 600 groundwater survey and engineering geology boreholes in Hanoi as well as the acceleration records of Imperial Valley earthquake in 1979 with magnitude M = 6.5, hypocenter of 26.5 km , and PGA of 0.169 g were chosen as input data for the research. By analyz ing geological conditions, tectonics, seismic characteristics of different soil types in Hanoi, a geological cross-section cutting through different engineering geology in Hanoi areas have been constructed. Numerical simulations of site effect at typical locations along the cross-section show: (i) The geological conditions on the surface of Hanoi clearly influence the earthquake ground motion, this is confirmed by the increase in the amplitude of the horizontal component of ground acceleration and the change of the strong vibrations from short to longer period. These effects obey a general rule, they become stronger when moving on the cross-section from west to east, corresponding to an increase in the thickness of the weak sedimentary layers covering the hard rock; and (ii) However, at t he place where the weak and soft soil layer appear (LK50 borehole), despite of the vibrations that are still converted from short to longer periods, the amplitude of the PGA is str ongly attenuated at the surface layer.